Historically consistent mass loss projections of the Greenland ice sheet - C. Rahlves; C. Rahlves; H. Goelzer; A. Born; P. M. Langebroek (The Cryosphere)
Mass loss from the Greenland ice sheet is a major contributor to global sea-level rise and is expected to intensify with ongoing Arctic warming. Given the threat of sea-level rise to coastal communities, accurately projecting future contributions from the Greenland ice sheet is crucial. This study evaluates the expected sea-level contribution from the ice sheet until 2100 by conducting an ensemble of standalone ice sheet simulations using the Community Ice Sheet Model (CISM). We initialize the ice sheet to closely match observed geometry by calibrating basal friction parameters and using regionally downscaled surface mass balance (SMB) forcing from various Earth system models (ESMs) and the ERA5 reanalysis. Using a historically consistent approach, we reduce model drift while closely reproducing observed mass loss over the historical period. We evaluate the effects of using absolute SMB values vs. prescribing SMB anomalies for future projections, identifying minimal differences in projected sea-level contributions. Our projections suggest sea-level contributions of 32 to 69 mm under SSP1-2.6 (Shared Socioeconomic Pathway), 44 to 119 mm under SSP2-4.5, and 74 to 228 mm under SSP5-8.5 by 2100. In our setup, variations in the initial state of the ice sheet only have a minimal impact on projected sea-level contributions, while climate forcing is a dominant source of uncertainty.